Isothermal step thickening in a long-spaced aliphatic polyester. (16th March 2020) - Marxsen, Stephanie F.; Häuβler, Manuel; Mecking, Stefan; Alamo, Rufina G.
Abstract: Discontinuous lamellar thickening has been found at the isothermal crystallization temperatures of a long-spaced aliphatic polyester (PE-48, 48) synthesized via polycondensation of the diol and diacid. The isothermal step thickening is characterized by a discrete increase in melting temperature with increasing crystallization time and an increase in heat of fusion of the high melting peak at the expense of the low melting peak. The increase in crystal thickness, quantified by SAXS, is consistent with a straightening of the chains at the basal surfaces of the lamellae to complete a full repeat of the crystalline layer. The increase in thickness and decrease in surface energy are associated with the sudden increase in crystal melting. The isothermal thickening follows a logarithmic dependence of time with a rate that increases with temperature. The thickening process is thermally activated and follows Arrhenius behavior with an activation energy of 238 ± 4 kJ/mol. Graphical abstract: Image 1 Highlights: Layered crystals of polyester, PE-48, 48 undergo step thickening during isothermal crystallization. Crystals with 2–3 layers thicken to complete 3 layers with increasing crystallization time. Isothermal step thickening leads to a discrete increase in melting temperature. Completion of the layer by chain straightening stabilizes the crystals. At high Tc, stable crystals with integer layers do not thicken.